171k views
5 votes
Hi! Can someone solve and tell me all the steps so I could understand how to do this?

Hi! Can someone solve and tell me all the steps so I could understand how to do this-example-1
User Torbatamas
by
5.2k points

1 Answer

1 vote

Answer:

x = 12

AB = 39

AC = 24

Explanation:

The sum of AB and BC is equal to the length of AC.

We can write the following equation based on this information :

AB + BC = AB rewrite the equation using given values

4x - 9 + 3x - 12 = 63 add like terms

7x - 21 = 63 add 21 to both sides

7x = 84 divide both sides by 7

x = 12 replace x with 12 in each expression to find the lengths

AB = 4x-9

AB = 4•12 - 9 and

AB = 39

BC = 3x -12

BC = 3•12-12 and

BC = 24

User Mamata Hegde
by
4.4k points